Los otros filósofos en Séneca - Otón Sobrino, Enrique (Cuadernos de Filología Clásica. Estudios Latinos, 2003)
Seneca claims Ion himself the liberty to bujíd his own mmd, not subordinated to other piel- Iosophical doctrines.